Emerging of bacterial resistance: an ongoing threat during and after the Syrian crisis - Basem Battah (Journal of Infection in Developing Countries)
The rapid emergence of bacterial resistance worldwide is a serious problem, leading to many therapeutic failures and rendering inactive effective antibiotics currently used . This problem has recently been accelerated by conflicts and its related migration. The antibiotic resistance phenomenon is diffused in Syria with a high rate of multi drug resistance cases in gram negative and gram positive organisms during and after the Syrian crisis as a result of misprescribing and overprescribing of antibiotics. The inappropriate use of antibiotic plays an important role in resistance generation. Hence, big efforts are urgently needed by using phenotypic and genetic analysis of bacterial strains against antibiotics to increase characterization and identification of mutant resistant strains and find new strategies to control the spread of antimicrobial resistance infections. This review highlights the antibacterial resistance problem in Syria, showing its negative impact and presenting a sum of efforts that are urgently needed to overcome this problem.